Electrical, morphological and surface roughness analysis of silver nanoparticles-filled epoxy conductive ink - Salim, Mohd Azli; Md. Saad, Adzni; Ahmad, Fauzi; Hamidi, Roshidah; Ali, Murni; Dai, Feng (Science and Technology Research Institute for Defence, 2021)
Conductive ink has become a potential alternative to replace the conventional circuitry in electronic applications. Due to this, various efforts have been conducted to obtain the optimum ink formulation that can fulfill the current demand. The objective of this study is to determine the performance of different formulations of silver nanoparticles-filled epoxy conductive ink with various filler loadings in terms of electrical conductivity. The main investigated parameter was the sheet resistance of the composition. The changes of morphology of the ink surface and surface roughness were also examined, which directly correlated to the sheet resistivity. The obtained results showed that the minimum threshold of silver nanoparticles (AgNP) filler required was 60 %wt for the ink to conduct electricity. However, this filler loading was not acceptable because of the wide dispersion of data. The ink filler loadings that can conduct electricity also showed the presence of granular particles on the ink layer surfaces, which also increased their surface roughness. The sheet resistance value also achieved a saturated value with filler loading of 90 %wt. It means that further addition of filler loading is not going to further improve the sheet resistivity of the composition. Based on this study, it can be summarised that the percentages of AgNP filler loadings of conductive ink that can fulfil the acceptable performance are between 70 to 90 %wt.